Making computer-generated scratch holograms from three-dimensional virtual models - Augier Calderín, Angel G.; Sánchez Pérez, Raul B. (Photonics Letters of Poland, 2010)
The scratch holography has been considered during many years by the optical community as a curiosity, being used only as an educational medium for teaching Optics. In this work we show the possibility of making more competitive the images that are obtained by this technique by means of hologravure. Hologravure is a way of making computer-generated scratch holograms from three-dimensional (3D) virtual models, represented as files in a 3D format by using appropriate software, and laser tracing on suitable material with a conventional computer driven CO2 engraver-laser system. Some interesting applications of hologravures are introduced and the corresponding reconstructing images are shown. Full text: PDF References: W.J. Beaty, Hand-drawn holograms, http://www.amasci.com/amateur/holo1.html H. Weil, Improvement in advertising and like signs, UK patent 37208/34 (December 1934). W. Plumber, L. Gardner, "A mechanically generated hologram?", Appl. Opt. 31, 6585 (1992). [CrossRef] J. Walker, "The Amateur Scientist", Scientific American 261, 106 (1989). [CrossRef] P. Kirkpatrick, "A Binocular Illusion", Am. J. Phys. 22, 492 (1954). [CrossRef] J. B. Lott, "Reflections on a gramophone record", Math. Gazette 47, 113 (1963). [CrossRef] J. Eichler, L. Dünkel, O. Gonçalves, "Three-Dimensional Image Construction by Curved Surface Scratches", Appl. Opt. 42, 5627 (2003). [CrossRef] W. Beaty, "Drawing holograms by hand", Proc. SPIE 5005, 156 (2003). [CrossRef] Scratch Holograms! http://www.instructables.com/id/Make-a-Tool-to-Draw-Scratch-Holograms!/ E. Garfield, "The World’s First Holographic Engraving", Essays of an Information Scientist 5, 348 (1981), http://www.garfield.library.upenn.edu/essays/v5p348y1981-82.pdf A.G.Augier, R.B. Sánchez, Opt. Commun. (2010), (in-press: doi 10.1016/joptcom.2010.09.008) [CrossRef] A.A. Kozma, D. L. Kelly, "Spatial Filtering for Detection of Signals Submerged in Noise", Appl. Opt. 4, 387 (1965). [CrossRef] L.P. Yaroslavskii and N.S. Merslakov, Methods of Digital Holography (Plenum Publishing Corporation, 1980). O. Bryngdal and F. Wyrowski, Digital holography-Computer generated holograms (E.Wolf (ed), Progress in Optics, Vol. XXVIII, Elsevier Science Publishers, 1990). http://www.holowiki.com/index.php/Scratch-O-Gram